Genome Wide Association Study and Next Generation Sequencing: A Glimmer of Light Toward New Possible Horizons in Frontotemporal Dementia Research - Ciani, Miriam; Benussi, Luisa; Bonvicini, Cristian; Ghidoni, Roberta (Frontiers in Neuroscience, 2019)
Frontotemporal Dementia (FTD) is a focal neurodegenerative disease with a strong genetic background, that causes early onset dementia. The present knowledge about the risk loci and causative mutations of FTD mainly derives from genetic linkage analysis, studies of candidate genes, Genome-Wide Association Studies (GWAS) and Next-Generation Sequencing (NGS) applications. In this review we report recent insights into the genetics of FTD, and, specifically, the results achieved thanks to GWAS and NGS approaches. Linkage studies of large FTD pedigrees have prompted the identification of causal mutations in different genes: mutations in C9orf72, MAPT and GRN genes explain the large majority of cases with a high family history of the disease. In cases with a less clear inheritance, GWAS and NGS have contributed to further understand the genetic picture of FTD. GWAS identified several common genetic variants with a modest risk effect. Of interest, many of these variants are in genes belonging to the endo-lysosomal pathway, the immune response and neuronal survival. On the opposite, the NGS approach allowed the identification of rare variants with a strong risk effect. These variants were identified in known FTD-associated genes and again in genes, involved in the endo-lysosomal pathway and in the immune response. Interestingly, both approaches demonstrated that several genes are associated to multiple neurodegenerative disorders including FTD. Thanks to these complementary approaches, the genetic picture of FTD is becoming more clear and novel key molecular processes are emerging. This will foster opportunities to move toward prevention and therapy for this incurable disease.